Front Cover: Mobil catalytic material number 41 modified magnetite nano‐composites for efficient extraction of non‐steroidal anti‐inflammatory drugs from tap water and urine samples. Issue 8 (23rd August 2022) - Kumar, Sandeep; Bhogal, Shikha; Sharma, Promila; Rani, Susheela; Aulakh, Jatinder Singh; Malik, Ashok Kumar
Abstract : DOI: 10.1002/sscp.202200026 This cover picture shows the applicability of Mobil catalytic material number 4 modified magnetite nano‐composites (MCM‐41@Fe3 O4 ) in magnetic solid phase extraction (MSPE). MCM‐41@Fe3 O4 as MSPE material was first added to the sample solution of NSAIDs containing diclofenac, ketoprofen, and mefenamic acid. After 5 min of incubation, the MCM‐41@Fe3 O4 can be separated using a magnetic field. Further, the supernatant of the solution was completely discarded, and the non‐steroidal anti‐inflammatory drugs were desorbed from MCM‐41@ Fe3 O4 . Finally, the eluent containing the mixture of analytes was analyzed by HPLC with photodiode array detection and the regenerated particles of MCM‐41@ Fe3 O4 would again be used for the next cycle.